Investigations on effect of FSW process parameter on hybrid Al MMC using Taguchi approach. (2021) - Narenthiran, B.; Paranthaman, P.
Abstract: In this research, stir casting method was adopted to developed hybrid aluminium composite with constant wt% of Boron nitride (2 wt%) and varying percentage of bagasse ash (4, 8, 12 wt%). Friction stir welding process was adopted for weldability analysis. Tool rotation speed, welding speed are selected as input parameter and impact strength of weld nugget was selected as output response. Taguchi method was adopted for designing experimental plan and to study the influence of input parameter over out response. Results revealed increase in reinforcement percentage showcase negative trends on impact strength; tool rotation speed has major contribution (48.5%) on output response. ANOVA results depicts that all the input parameter has significant over output response.